Application of the Learning Function in Realizing the Goals of the Ma'had Al-Islamiah Bandung Institution - Muchtarom, Muchtarom; Kumar, Saurav (The International Journal of Education Management and Sociology, 2024)
The research aims to describe the implementation of the learning function in Ma'had Al-Islamiyah. Knowing the factors inhibiting the implementation of learning at Ma'had Al-Islamiyah. Knowing the solutions to obstacles to implementing learning in realizing the goals of the institution at Ma'had Al-Islamiyah. This research method uses a qualitative approach that describes research field phenomena. Data collection techniques through observation, interviews, and documentation studies. Conclusion In learning activities there are management functions that must be carried out, such as planning learning, organizing learning, implementing learning, and monitoring accompanied by learning evaluation. The inhibiting factor is that in planning the implementation of learning, the teachers do not know how to make it. Solutions in the learning implementation plan, are to be prepared so that the learning process can be realized according to the objectives of the Al-Islamiyah Ma'had institution.